Specific exercise testing in judo athletes - Pocecco, E.; Gatterer, H.; Ruedl, G.; Burtscher, M. (Archives of Budo, 2012)
Background and Study Aim: All-out exercise tests lasting the duration of a judo match, i.e., 5 minutes, regarding arm and leg performance have barely been introduced. We hypothesised that, besides body composition, arm and leg performance, derived from 5 minutes lasting all-out ergometric tests, would be of importance for success in judo competitions. Material and Methods: The groups investigated consisted of eight juvenile (15.3±0.9 years) and six adult (25.2±4.9 years) male Austrian judokas of different ranks. In addition to body composition, power output and peak oxygen uptake (VO2peak) were determined during 5-min all-out tests on an arm crank and a cycle ergometer. Results: Relative VO2peak during cranking was about 18% higher in juvenile than in adult men (35.5±4.3 ml/kg·min vs. 30.0±3.5 ml/kg·min, p=0.05). However, neither body composition nor arm and leg performance was related to competition success in juvenile judo athletes. In contrast, in adult judokas percentage of body fat (r=-0.83) and relative maximum arm power (r=0.83) were both related to competition rank (p=0.05). Conclusions: As these results indicate age-related differences in the assessed determinants of success for judo competition performance, they may have practical importance and should be considered in planning the training for male judo athletes of different age classes.